“There’s a lot of woman in him”: the feminine as a deviance from the norm - Moura, Renan Gomes de; Nascimento, Rejane Prevot; Barros, Denise Franca (Organizações & Sociedade, 2020)
This article seeks to understand how femininity is understood by organizations from the perspective of masculine homosexuals, with a special focus on the concept of Ableism. In this qualitative research, data was collected through in-depth interviews with 13 masculine homosexuals living in the state of Rio de Janeiro and the corpus was analysed using Content Analysis (Bardin, 2009). Our field research showed that effeminate gays and women are considered to be inferior to those people with heteromasculine behavior. In this context, femininity within the organizational environment is considered as a deficiency, and those who have this deficiency are excluded from this environment or encouraged to overcome this deficiency.